Suppressing Manganese Dissolution from Lithium Manganese Oxide Spinel Cathodes with Single‐Layer Graphene. Issue 17 (24th June 2015) - Jaber‐Ansari, Laila; Puntambekar, Kanan P.; Kim, Soo; Aykol, Muratahan; Luo, Langli; Wu, Jinsong; Myers, Benjamin D.; Iddir, Hakim; Russell, John T.; Saldaña, Spencer J.; Kumar, Rajan; Thackeray, Michael M.; et al.
<x xml:space="preserve">Abstract</x> Spinel‐structured LiMn2O4 (LMO) is a desirable cathode material for Li‐ion batteries due to its low cost, abundance, and high power capability. However, LMO suffers from limited cycle life that is triggered by manganese dissolution into the electrolyte during electrochemical cycling. Here, it is shown that single‐layer graphene coatings suppress manganese dissolution, thus enhancing the performance and lifetime of LMO cathodes. Relative to lithium cells with uncoated LMO cathodes, cells with graphene‐coated LMO cathodes provide improved capacity retention with enhanced cycling stability. X‐ray photoelectron spectroscopy reveals that graphene coatings inhibit manganese depletion from the LMO surface. Additionally, transmission electron microscopy demonstrates that a stable solid electrolyte interphase is formed on graphene, which screens the LMO from direct contact with the electrolyte. Density functional theory calculations provide two mechanisms for the role of graphene in the suppression of manganese dissolution. First, common defects in single‐layer graphene are found to allow the transport of lithium while concurrently acting as barriers for manganese diffusion. Second, graphene can chemically interact with Mn3+ at the LMO electrode surface, promoting an oxidation state change to Mn4+, which suppresses dissolution.